ESR1 mutations: a new biomarker in breast cancer. (3rd July 2019) - Carausu, Marcela; Bidard, François-Clément; Callens, Celine; Melaabi, Samia; Jeannot, Emmanuelle; Pierga, Jean-Yves; Cabel, Luc
ABSTRACT: Introduction : In hormone receptor-positive breast cancer, ESR1 mutations have emerged as a key mechanism of resistance to endocrine therapy. Areas covered : Here, we review currently available data on ESR1 mutations, regarding their functional impact, prevalence at different stages (and according to the material used: tissue-based analysis vs. liquid biopsy), prognostic impact and predictive value of resistance to aromatase inhibitors. Possible strategies to overcome this resistance by using selective estrogen receptor downregulators (such as fulvestrant) are also discussed. Expert opinion : ESR1 mutation detection will probably become a prognostic and predictive biomarker in the future, used in clinical practice for hormone-receptor breast cancer, especially in the metastatic setting. In the future, we should expect to assess ESR1 mutations, using liquid biopsy (by digital-PCR or next-generation sequencing), in the same way as other prognostic or predictive biomarkers, such as EGFR mutations in lung cancer, and possibly even have targeted-therapies against these mutations.